Small bowel transplantation in outbred rats - Waisberg,Daniel Reis (2011)
PURPOSE: To investigate the clinical evolution of orthotopic small bowel transplantation in outbred rats. METHODS: Seventy-two outbred Wistar rats weighting from 250 to 300g were used as donor and recipient in 36 consecutives ortothopic small intestine transplantation without immunosuppression. The graft was transplanted into the recipient using end-to-side aortic and portacaval microvascular anastomosis. Procedure duration, animal clinical course and survival were evaluated. Survival shorter than four days was considered technical failure. Recipients were sacrificed with signs of severe graft rejection or survival longer than 120 days. Necropsies were performed in all recipients to access histopathological changes in the graft. RESULTS: Median time for the procedure was 107 minutes. Six recipients (16.7%) presented technical failure. Twenty-seven recipients were sacrificed due to rejection, being nineteen (52.7%) between 7th and 15th postoperative day and eight (22.2%) between 34th and 47th postoperative day. Graft histology confirmed severe acute cellular rejection in those recipients. Uneventful evolution and survival longer than 120 days without rejection were observed in three recipients (8.3%). CONCLUSION: Intestinal transplantation in outbred rats without immunosuppressant regiment accomplishes variable clinical evolution.